2012
DOI: 10.1111/j.1444-0938.2012.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation counselling practices among Québec optometrists: evaluating beliefs, practices, barriers and needs

Abstract: Background:  Despite the fact that cigarette smoking is a well known risk factor for many ocular diseases, very little data exist regarding optometrists' interventions in smoking cessation counselling with their patients. The aim of this study was to evaluate the practices, perceptions and educational needs of Québec optometrists regarding smoking cessation counselling. Methods:  A self‐administered questionnaire pertaining to smoking cessation counselling practices was mailed to 600 optometrists licensed in Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, only a third of respondents in the current survey reported that they regularly took a smoking history in new patients and a similar number were proactive in advising on smoking cessation. Previous studies that have investigated the attitudes and practice of optometrists in this area have reported similar findings [30,31]. These studies also identified a number of barriers to routinely addressing a patient’s smoking behaviour including time constraints and a perceived need for further training in this area [31].…”
Section: Discussionmentioning
confidence: 57%
“…However, only a third of respondents in the current survey reported that they regularly took a smoking history in new patients and a similar number were proactive in advising on smoking cessation. Previous studies that have investigated the attitudes and practice of optometrists in this area have reported similar findings [30,31]. These studies also identified a number of barriers to routinely addressing a patient’s smoking behaviour including time constraints and a perceived need for further training in this area [31].…”
Section: Discussionmentioning
confidence: 57%
“…31 A 2012 study of 306 optometrists in Quebec (Canada) reported that most respondents (90%) were aware of some ocular diseases related to smoking; however, few advised patients to stop smoking (29%). 32 A qualitative pilot study conducted in 2009 of 11 optometrists in southwestern Ontario found that participants were well aware of the associations of smoking with eye diseases such as AMD and advised patients who smoked about these risks; however, few systematically asked their patients about specific smoking behavior or interest in quitting. The optometrists in the study had neither referred patients to smoking cessation telephone quitlines and community-based services nor provided specific prevention messaging to younger patients about smoking and eye health.…”
mentioning
confidence: 99%
“…Reports have shown Québec optometrists are well aware of the effects of smoking on ocular health and of the importance of educating their patients. In addition, they believe it is their role to enquire about the smoking status of patients and to recommend that they stop smoking . Care should be taken to inform optometrists they should take time to educate their non‐smoking, teenage patients as well.…”
Section: Resultsmentioning
confidence: 99%